Ortho-topolin-9-glucoside, an aromatic cytokinin from Populus x canadensis cv Robusta leaves. - Strnad, M.; Peters, W.; Hanus, J.; Beck, E.
A new natural cytokinin was isolated from Populus x canadensis Moench cv Robusta leaves. Its structure was established as N6-(o-hydroxybenzylamino-9-O-?-d-glucopyranosylpurine (termed ortho-topolin-9-glucoside)by UV and mass spectrometry and confirmed by synthesis. This cytokinin exhibited comparatively low biological activity in three common bioassays. It was quantified in the leaf extract by combined high performance liquid chromatography-enzyme linked immunoassay. Amounting to 50 pmol g?1 fresh weight, ortho-topolin-9-glucoside was the dominant aromatic cytokinin in poplar leaves collected 2 hr after sunrise.
Keywords: POPULUS X CANADENSIS MOENCH CV ROBUST; POPLAR; SALICACEAE; AROMATIC CYTOKININ; ND O-HYDROXYBENZYLAMINO-9-O-?-D-GLUCOPYRANOSYLPURINE; ORTHO-TOPOLIN-9-GLUCOSIDE.